2013
DOI: 10.3121/cmr.2013.1136
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Willingness to Participate in Window-of-Opportunity Breast Trials

Abstract: Objective: We conducted a pilot survey to evaluate breast cancer patients' willingness to participate in a preoperative chemoprevention (ie, window-of-opportunity) study. Design:A 27-question written survey was developed and administered to participants. Setting:A breast cancer specialty clinic at the University of Wisconsin Hospital and Clinics.Participants: 30 adult patients with newly diagnosed operable breast cancer participated after signing informed consent.Methods: A convenience sample of 30 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
5
0
4
Order By: Relevance
“…One study found that only 26.7% of patients with newly diagnosed operable breast cancer were agreeable to participate in WOT trials. 39 Hence trials with limited additional investigation and biopsies which can be incorporated into a patient's routine work flow prior to surgery will likely have a higher participation rate. Finally, and most importantly, precise co-ordination and good communication within the multidisciplinary team is mandatory.…”
Section: Optimal Wot Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that only 26.7% of patients with newly diagnosed operable breast cancer were agreeable to participate in WOT trials. 39 Hence trials with limited additional investigation and biopsies which can be incorporated into a patient's routine work flow prior to surgery will likely have a higher participation rate. Finally, and most importantly, precise co-ordination and good communication within the multidisciplinary team is mandatory.…”
Section: Optimal Wot Trial Designmentioning
confidence: 99%
“…Study recruitment can be hindered by the need for an additional pre‐treatment research biopsy and in some cases serial preoperative imaging, which may dis‐incentivize patients. One study found that only 26.7% of patients with newly diagnosed operable breast cancer were agreeable to participate in WOT trials . Hence trials with limited additional investigation and biopsies which can be incorporated into a patient's routine work flow prior to surgery will likely have a higher participation rate.…”
Section: Introductionmentioning
confidence: 99%
“…참여 의향의 측정은 실제 임상시험에 참여한 자를 참여 의 향이 있다고 간주하거나 (n = 6) 6,11,12,[16][17][18] , 참여 의향이 있 음, 없음, 잘 모르겠음으로 응답하도록 개발된 설문도구를 이용하여 질문하거나 (n = 2) 7,13) , 4점 혹은 5점의 리커트 척 도로 측정한 참여 의향을 예 또는 아니오로 이분화하거나 (n = 3) 5,8,10) , 10점 만점의 시각상사척도상 참여 의향이 얼 마나 있는지 9) 물어보는 식으로 이루어졌다. 각 연구별로 보 고한 참여 의향의 분율은 11.1 %~88.3 % 까지 다양하였다 (중앙값 48.6 %).…”
Section: 참여의향unclassified
“…참여 의향과 연관된 요인으로는 환자 관련 요인이 가장 많았으며 이를 인구사회학적 요인, 임상적 요인, 경험, 태 도, 인식과 관련된 요인으로 세분하였다. 인구사회학적 요 인으로는 참여자의 연령 6,11,16) , 인종 11,16) , 성별 9,17) , 교육 수준 10,13) , 가족관계 (자녀와 생활을 함께 하는 경우 5) , 혼인 상태 6) , 독거 6) , 재정적 어려움 5) 등이 보고되었다. 임상적 요인으 로는 암 진단 후 임상시험 참여 제안을 받은 시점 11,16) , 암 치 료 시작 후 임상시험 참여 제안을 받은 시점 11) , 암의 종류 16) , 불안 경향 5) , 동반 상병 유무 6) , 피로감 6) , 암 치료를 받았던 기존 경험 6,8,10) 등이 보고되었다.…”
Section: 참여의향의연관요인unclassified
See 1 more Smart Citation